Implementation of the Hill Cipher Algorithm with a Random Generator in Key Validation for File Security - Azmi, Fauzul; Tommy, Tommy (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
Digital file security plays a crucial role in the modern era of rapid information exchange and growing data threats. This study presents the development of a desktop-based file security system that utilizes a random key matrix approach for secure encryption and decryption. The core innovation lies in the validation of randomly generated key matrices to ensure they possess a valid inverse under modulo 256 arithmetic. This validation is critical, as it guarantees that encrypted data can be accurately decrypted using the same key. The system converts digital files into binary blocks, which are then encrypted through matrix multiplication with the validated key. Comprehensive testing was carried out using various file types and sizes to evaluate the system’s robustness, performance, and reliability. The results demonstrate that the application provides an effective method for safeguarding digital files, with improved security due to the randomness and strength of the key generation process. This research contributes significantly to the ongoing advancement of cryptography-based solutions for file protection in desktop environments.